Introduction to the special issue: The WHO World Mental Health International College Student (WMH‐ICS) initiative. Issue 2 (9th January 2019) - Cuijpers, Pim; Auerbach, Randy P.; Benjet, Corina; Bruffaerts, Ronny; Ebert, David; Karyotaki, Eirini; Kessler, Ronald C.
Abstract: Most mental disorders have their first onset in early adulthood. Epidemiological research, as well as research on preventive and early interventions, is therefore very important. This thematic issue focuses on one of the first systematic attempts to develop such services for college students. The WHO World Mental Health International College Student (WMH‐ICS) initiative is based on the largest and continuously growing epidemiological dataset ever collected in college students. Based on these results, the initiative has now started to implement internet‐based interventions for common mental disorders and emotional problems. In this special issue, a general paper about the initiative is presented, as well as a paper on the implementation of the WMH‐ICS initiative in low and middle income countries. It also includes several papers with core epidemiological results of the initiative, a meta‐analysis of internet‐based interventions for mental health problems in college students and the first results of trials conducted as part of the initiative. Taken together, the papers in this special issue show that WMH‐ICS is on its way to becoming a major initiative in addressing the problem of unmet need for treatment of mental health problems among college students.